Pengaruh Strategi Pembelajaran CTL Dan Media Berbasis AI Terhadap Kemampuan Literasi Mahasiswa Tadris IPS UINSU Dalam Penelitian Kuantitatif - Tarigan, Khairan Syahputra; Perkasa, Ripho Delzy (Cetta: Jurnal Ilmu Pendidikan, 2024)
Education in the modern era is experiencing significant transformation, including changes in technology and teaching paradigms. At the North Sumatra State Islamic University (UINSU), especially in the Tadris Social Sciences (IPS) study program, there are challenges in developing student literacy, especially in Quantitative Research courses. This research aims to analyze the effect of implementing Contextual Teaching and Learning (CTL) learning strategies and Artificial Intelligence (AI)-based learning media on students' literacy abilities. The research method used was quantitative with a 2x2 factorial quasi-experimental design, involving 68 students divided into experimental and control classes. Data was collected through questionnaires and analyzed using multiple regression analysis, t test, and F test. The results showed that the application of CTL strategies and AI media had a significant positive effect on students' literacy skills, with a contribution of 77.7%. These findings emphasize the importance of integrating interactive learning strategies and technology in improving academic literacy. The conclusions of this research suggest the need for further development and application of innovative learning methods to achieve more optimal results in student literacy.